"Genes for a role, " "genes as essences": Secondary students' explicit and implicit intuitions about genetic essentialism and teleology. Issue 2 (23rd July 2022) - Stern, Florian; Kampourakis, Kostas; Müller, Andreas
Abstract: Biology education research has shown that deeply rooted intuitions can influence students' understanding of biological phenomena. One example is design teleology, the intuition that organisms' traits were designed to fulfill a goal. Another example is psychological essentialism, the intuition that organisms have fixed essences. Past research has found both of these intuitions to be conceptual obstacles for understanding evolution. In our study, we investigated whether conceptions stemming from these two intuitions are also expressed in the context of genetics. So, we used two tests to identify teleology and essentialism conceptions in the context of genetics: a multiple‐choice questionnaire (Genetic Essentialism and Teleology Questionnaire) and an implicit test (Genetic Essentialism and Teleology Implicit Association Test [IAT]). The development and validation process of these two tests are presented elsewhere. The present article presents the results of the administration of both tests to 332 secondary school students. It was found that: (1) those students exhibited teleology and essentialism conceptions in the context of genetics; the former, but not the latter, were less frequent the older students were; (2) teleology and essentialism conceptions were not correlated; and (3) measures from the explicit and implicit tests were not correlated with each other. Recommendations to improve teaching about genetics are made; for instance, we suggest that students' genetic essentialism conceptions could be addressed by emphasizing the existence of variation within populations and species, and the impact of mutations on phenotypic outcomes. We also recommend that teachers address design teleology and psychological essentialism conceptions independently from each other.